"Homework feedback is...": Elementary and middle school teachers' conceptions of homework feedback - Cunha, Jennifer (2018)
This study explored mathematics teachers' conceptions of the homework feedback focusing on four key aspects: definition, purpose, types, and perceived impact. Forty-seven teachers from elementary and middle schools participated in six focus groups. Data were analyzed using content analysis. To enhance the trustworthiness of findings, classroom observations were used for triangulation of data. Participants conceptualized homework feedback in three directions (i.e., teachers' feedback provided to students, students' feedback provided to teachers, and homework self-feedback), being teachers' monitoring of students' learning the purpose reported by most teachers. Participants also reported the types of homework feedback more frequently used in class (e.g., checking homework completion, checking homework on the board), and their perceived impact on students. Findings provide valuable information to deepen the understanding of the homework feedback process, which may help develop new avenues for future research.